Oligogenic inheritance of optineurin (OPTN) and C9ORF72 mutations in ALS highlights localisation of OPTN in the TDP‐43‐negative inclusions of C9ORF72‐ALS. Issue 2 (24th August 2015) - Bury, Joanna J.; Highley, J. Robin; Cooper‐Knock, Johnathan; Goodall, Emily F.; Higginbottom, Adrian; McDermott, Christopher J.; Ince, Paul G.; Shaw, Pamela J.; Kirby, Janine
Abstract : Amyotrophic lateral sclerosis (ALS) is characterized by motor neurone loss resulting in muscle weakness, spasticity and ultimately death. 5‐10% are caused by inherited mutations, most commonly C9ORF72, SOD1, TARDBP and FUS . Rarer genetic causes of ALS include mutation of optineurin (mt OPTN ). Furthermore, optineurin protein has been localized to the ubiquitylated aggregates in several neurodegenerative diseases, including ALS. This study: (i) investigated the frequency of mt OPTN in ALS patients in England; (ii) characterized the clinical and neuropathological features of ALS associated with a mt OPTN ; and (iii) investigated optineurin neuropathology in C9ORF72 ‐related ALS ( C9ORF72 ‐ALS). We identified a heterozygous p.E322K missense mutation in exon 10 of OPTN in one familial ALS patient who additionally had a C9ORF72 mutation. This patient had bulbar, limb and respiratory disease without cognitive problems. Neuropathology revealed motor neurone loss, trans‐activation response DNA protein 43 (TDP‐43)‐positive neuronal and glial cytoplasmic inclusions together with TDP‐43‐negative neuronal cytoplasmic inclusions in extra motor regions that are characteristic of C9ORF72 ‐ALS. We have demonstrated that both TDP‐43‐positive and negative inclusion types had positive staining for optineurin by immunohistochemistry. We went on to show that optineurin was present in TDP‐43‐negative cytoplasmic extra motor inclusions in C9ORF72 ‐ALS cases that do not carry mt OPTN . We conclude that: (i) OPTN mutations are associated with ALS; (ii) optineurin protein is present in a subset of the extramotor inclusions of C9ORF72 ‐ALS; (iii) It is not uncommon for multiple ALS‐causing mutations to occur in the same patient; and (iv) studies of optineurin are likely to provide useful dataregarding the pathophysiology of ALS and neurodegeneration.